PENGGUNAAN MODEL PEMBELAJARAN DIRECT LEARNING TERHADAP KEMAMPUAN MENULIS IKLAN DAN POSTER OLEH SISWA KELAS VIII SMP NEGERI 2 PADANGSIDIMPUAN - Herawati Parapat, Lili; Lubis, KHatib; Sitompul, Yeti (Linguistik : Jurnal Bahasa dan Sastra, 2023)
Learning to write in schools is a means to develop writing skills because the success of students taking lessons at school is largely determined by writing skills. Therefore, writing skills are very important for subjects. Writing skills are not only needed when someone is still in school. This study limits the problem to the Influence of Direct Learning Learning Model on the Ability to Write Advertisements and Posters by Class VIII Students of SMP Negeri 2 Padangsidimpuan. Samples were taken from class VIII-9 male totaling 17 students, female totaling 15 students, so the total sample amounted to 32 students. This means that the comparison of rxy and rtable values is (0.6830.341).